Intestinal Obstruction by Meckel’s Diverticulum in a 92 Years Old Woman - Maryam Sarkardeh; Seyed Javad Davari Sani (Case Reports in Surgery)
Background. Meckel’s diverticulum is a vestigial remnant of the omphalomesenteric duct that in most cases (53%) is diagnosed in the first two years of life. Case report. A variety of complications are related to Meckel’s diverticulum including bleeding, intestinal obstruction, but in adults, the most important complication is intestinal obstruction. We reported Meckel’s diverticulum in a 92-year-old woman with symptoms of intestinal obstruction including abdominal pain, vomitus, and abdominal distention who referred to the hospital emergency. Imaging findings showed intestinal obstruction and laparotomy showed that the cause of intestinal obstruction was Meckel’s diverticulum. Finally, Meckel’s diverticulum was resected and the patient recovered. Conclusion. Intestinal obstruction because of a large Meckel’s diverticulum in an elderly woman is rare and requires a high attention for diagnosis, and it is almost discovered by surgery.